So 8x+4+4x+8=15x-9
Combine like terms.
12x+12=15x-9
Add 9 to both sides.
12x+21=15x
Subtract 12 from both sides.
21=3x
Divide both sides by 3.
x=7
Now plug in 7 for x in 8x+4.
8(7)+4
56+4
=60
Answer:
582.1
Step-by-step explanation:
Answer:
f(-5) = 0
Step-by-step explanation:
Step 1: Define
f(x) = -2x² - 10x
f(-5) is x = -5
Step 2: Substitute and Evaluate
f(-5) = -2(-5)² - 10(-5)
f(-5) = -2(25) + 50
f(-5) = -50 + 50
f(-5) = 0
With 5lbs of sugar syrup to get a 25% syrup you would need to add 15lbs of water
(8x 2 −15x)−(x 2 −27x)=ax 2 +bxleft parenthesis, 8, x, squared, minus, 15, x, right parenthesis, minus, left parenthesis, x, squ
quester [9]
Answer:
<h2>5</h2>
Step-by-step explanation:
Given the expression (8x² −15x)−(x² −27x) = ax² +bx, we are to determine the value of b-a. Before we determine the vwlue of b-a, we need to first calculate for the value of a and b from the given expression.
On expanding the left hand side of the expression we have;
= (8x² −15x)−(x² −27x)
Open the paranthesis
= 8x² −15x−x²+27x
collect the like terms
= 8x²−x²+27x −15x
= 7x²+12x
Comparing the resulting expression with ax²+bx
7x²+12x = ax²+bx
7x² = ax²
a = 7
Also;
12x = bx
b =12
The value of b - a = 12 - 7
b -a = 5
Hence the value of b-a is equivalent to 5